Primary treatments for clinically localised prostate cancer: a comprehensive lifetime cost‐utility analysis. (28th December 2012) - Cooperberg, Matthew R.; Ramakrishna, Naren R.; Duff, Steven B.; Hughes, Kathleen E.; Sadownik, Sara; Smith, Joseph A.; Tewari, Ashutosh K.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Multiple treatment alternatives exist for localised prostate cancer, with few high‐quality studies directly comparing their comparative effectiveness and costs. The present study is the most comprehensive cost‐effectiveness analysis to date for localised prostate cancer, conducted with a lifetime horizon and accounting for survival, health‐related quality‐of‐life, and cost impact of secondary treatments and other downstream events, as well as primary treatment choices. The analysis found minor differences, generally slightly favouring surgical methods, in quality‐adjusted life years across treatment options. However, radiation therapy (RT) was consistently more expensive than surgery, and some alternatives, e.g. intensity‐modulated RT for low‐risk disease, were dominated – that is, both more expensive and less effective than competing alternatives. Objective To characterise the costs and outcomes associated with radical prostatectomy (open, laparoscopic, or robot‐assisted) and radiation therapy (RT: dose‐escalated three‐dimensional conformal RT, intensity‐modulated RT, brachytherapy, or combination), using a comprehensive, lifetime decision analytical model. Patients and Methods A Markov model was constructed to follow hypothetical men with low‐, intermediate‐, and high‐risk prostate cancer over their lifetimes after primary treatment; probabilities of outcomes were based on an exhaustive literature search yielding 232 unique publications. In each Markov cycle, patients could have remission, recurrence, salvage treatment, metastasis, death from prostate cancer, and death from other causes. Utilities for each health state were determined, and disutilities were applied for complications and toxicities of treatment. Costs were determined from the USA payer perspective, with incorporation of patient costs in a sensitivity analysis. Results Differences across treatments in quality‐adjusted life years across methods were modest, ranging from 10.3 to 11.3 for low‐risk patients, 9.6–10.5 for intermediate‐risk patients and 7.8–9.3 for high‐risk patients. There were no statistically significant differences among surgical methods, which tended to be more effective than RT methods, with the exception of combined external beam + brachytherapy for high‐risk disease. RT methods were consistently more expensive than surgical methods; costs ranged from 19 901 (robot‐assisted prostatectomy for low‐risk disease) to 50 276 (combined RT for high‐risk disease). These findings were robust to an extensive set of sensitivity analyses. Conclusions Our analysis found small differences in outcomes and substantial differences in payer and patient costs across treatment alternatives. These findings may inform future policy discussions about strategies to improve efficiency of treatment selection for localised prostate cancer.